Genomics and evolution of microbial eukaryotes - Katz, Laura Katz (Oxford University Press, 2006)
This book presents analyses and interpretations from experts in the field. Recent advances, particularly in DNA sequencing technologies, have made eukaryotic microbes more accessible through genome analyses. Unravelling the wealth of information on eukaryotic genomes will invariably revolutionize our understanding of eukaryotes, including their physiology, systematics, and ecology